Ammonia Gas Sensing Characteristics of Spin Coated Polyaniline Films - Bavane, Ravindra Kumar G.; Mahajan, Ashok M.; Shirsat, Mahendra D.; Gore, Ratnakar B. (JOURNAL OF ADVANCES IN PHYSICS, 2013)
The conductive layer of emeraldine base polyaniline (PANI) thin film coated on silicon has successfully tested for ammonia. The bulk PANI powder was synthesized by oxidative polymerization of aniline using ammonium peroxidisulfate in an acidic medium and dissolved in N-methyl pyrrolidone (NMP) for coating the thin film on Silicon using spin coater. FTIR, UVvisible, and SEM were used to characterize the PANI thin film. The electrical conductivity of the PANI films has been studied by measuring the change in electrical conductivity by Four Probe Set up on exposure to ammonia gas (NH3) at different concentrations from 100 ppm to 500 ppm. margin.